Taliban in Afghanistan, Present and Future: In Search of an Inclusive, Peaceful, Welfare and Sovereign Nation State? - Sahrasad, Herdi; Chaidar, Al; Bayhaki, Imron; Tabrani, Dedy; Mulky, Mohamad Asrori; Ridwan, Muhammad (Budapest International Research and Critics University, 2021)
The Taliban government is in the world spotlight despite its pledge to aim only at a peaceful, inclusive and sovereign